2023
DOI: 10.3390/cancers15030900
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Resection for Metastatic Colorectal, Gastric and Pancreatic Cancer Patients: In Search of Scientific Evidence to Inform Clinical Practice

Abstract: The management of the primary tumor in metastatic colorectal, gastric and pancreatic cancer patients may be challenging. Indeed, primary tumor progression could be associated with severe symptoms, compromising the quality of life and the feasibility of effective systemic therapy, and might result in life-threatening complications. While retrospective series have suggested that surgery on the primary tumor may confer a survival advantage even in asymptomatic patients, randomized trials seem not to definitively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 140 publications
0
7
0
Order By: Relevance
“…Our results showed that the CEUS mode and quantitative parameters differed among the different hepatic metastasis groups in PDAC ( Figure 5 ), where the WIS ratio may be an important factor in assessing the risk of hepatic metastasis. The presence of hepatic metastases is an important independent prognostic factor for PDAC ( 18 ). Unfortunately, in current medical developments, it can only be accurately assessed at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the CEUS mode and quantitative parameters differed among the different hepatic metastasis groups in PDAC ( Figure 5 ), where the WIS ratio may be an important factor in assessing the risk of hepatic metastasis. The presence of hepatic metastases is an important independent prognostic factor for PDAC ( 18 ). Unfortunately, in current medical developments, it can only be accurately assessed at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…], serum tumor marker detection, US, and contrastenhanced computed tomography (CECT). When CECT was still unable to determine the nature of the liver mass, dynamic MRI 18 F-fluorodeoxyglucose (18F-FDG) positron emission tomography-computed tomography (PET-CT) imaging was chosen.…”
Section: Patientsmentioning
confidence: 99%
“…Our analysis fits into the broad and controversial scenario of the management of primary tumor in synchronous metastatic CRC patients. While in the case of symptomatic primary tumors, the indication for surgery is a need rather than a choice, in the case of asymptomatic primary tumors, literature data are conflicting about the benefit of PTR in terms of survival [12,[15][16][17][18][19][20], as demonstrated by two recent meta-analyses mainly including nonrandomized, single-center, retrospective studies that came to opposite conclusions [19,20]. Notably, an intrinsic high risk of selection bias affected these analyses, together with the lack of data about QoL, administered treatments, reason for resection/no resection, baseline disease status, biological profile, and prognostic factor related to each individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Major guidelines currently recommend PTR in metastatic CRC patients only in the presence of overt symptoms or in the case of high risk of their imminent onset, while systemic treatment is recommended as the preferred initial step for asymptomatic patients [1,10,11], though it must be acknowledged that the management of the primary tumor is still an open issue [12]. Here, we present the results of a pooled analysis of two prospective, open-label, multicentric phase III randomized trials, TRIBE (NCT00719797) and TRIBE2 (NCT02339116), where untreated metastatic CRC patients received upfront chemotherapy (FOLFOXIRI, FOLFOX, or FOLFIRI) plus bevacizumab (bev).…”
Section: Introductionmentioning
confidence: 99%
“…The principal therapeutic strategy for mCRC (Metastatic colorectal cancer) patients is palliative chemotherapy, at the same time, non-systematic therapy (such as surgery and optional radiation and ablative techniques) is optional for patients with respectable metastatic lesions to improve survival [2]. The early-stage primary disease typically requires laparoscopic surgery; cases involving metastases necessitate open surgery for tumor resection, and nonresectable cases typically require adjuvant radiotherapy [3]. Neoadjuvant and palliative chemotherapies [4], immunotherapy [5], and tyrosine kinase inhibitor (TKI) [6] therapy are additional CRC treatments.…”
Section: Introductionmentioning
confidence: 99%